(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article comprehensively analyzes the formation, stages of development and scientific heritage of the Central Asian archaeological school, which was formed on the basis of the Department of Central Asian Archaeology at the Faculty of History of Tashkent State University (now the National University of Uzbekistan). The purpose of the study is to reveal the content of the scientific traditions developed by Mikhail Evgenievich Masson, the methodological foundations of its 20 fundamental principles and their significance in modern archaeological science. The study used historical-analytical, comparative and source-based methods.